Unravelling the Complete Raman Response of Graphene Nanoribbons Discerning the Signature of Edge Passivation. Issue 8 (22nd June 2022) - Milotti, Valeria; Berkmann, Claudia; Laranjeira, Jorge; Cui, Weili; Cao, Kecheng; Zhang, Yifan; Kaiser, Ute; Yanagi, Kazuhiro; Melle‐Franco, Manuel; Shi, Lei; Pichler, Thomas; Ayala, Paola
Abstract: Controlling the edge morphology and terminations of graphene nanoribbons (GNR) allows tailoring their electronic properties and boosts their application potential. One way of making such structures is encapsulating them inside single‐walled carbon nanotubes. Despite the versatility of Raman spectroscopy to resolve strong spectral signals of these systems, discerning the response of long nanoribbons from that of any residual precursor remaining outside after synthesis has been so far elusive. Here, the terrylene dye is used as precursor to make long and ultra‐narrow armchair‐edged GNR inside nanotubes. The alignment and characteristic length of terrylene encapsulated parallel to the tube's axis facilitates the ribbon formation via polymerization, with high stability up to 750 °C when the hybrid system is kept in high vacuum. A high temperature annealing is used to remove the terrylene external molecules and a subtraction model based on the determination of a scaling factor related to the G‐band response of the system is developed. This not only represents a critical step forward toward the analysis of the nanoribbon‐nanotube system, but it is a study that enables unraveling the Raman signatures of the individual CH‐modes (the signature of edge passivation) for GNR for the first time with unprecedented detail. Abstract : To make encapsulated nanoribbons useful, their edge morphology needs to be precisely understood. Here terrylene is used as a precursor to make long and ultra‐narrow armchair‐edged graphene nanoribbons inside carbon nanotubes. This study unravels the Raman signatures of the individual CH‐modes (the signature of edge passivation) for graphene nanoribbons with unprecedented detail.